2006
DOI: 10.1002/pola.21368
|View full text |Cite
|
Sign up to set email alerts
|

PAMAMOS: The first commercial silicon‐containing dendrimers and their applications

Abstract: ABSTRACT:The world of dendrimers presently encompasses several thousands of publications, including scientific papers and patents, several hundreds of different compositions, but only a few commercially available families of products (i.e. polyamidoamines (PAMAMs), until recently polypropyleneimines, and phosphorus-containing dendrimers) This is the story of PAMAMOS, which recently became the first commercially available silicon-containing dendrimers, and how we journeyed from our initial idea to the point of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…13 C NMR spectra showed that the signals for δ SiCH 3 appeared at 0.1 ppm, for δ SiCH 2 at 14.1 ppm, δ -CH 2 of the Si-CH 2 -CH 2 -CH 2 -group appeared at 23.5 and 74.5 ppm, δ SiCH 2 of the oxirane ring at 44.6 ppm, δ CH 2 of the O-CH 2 -oxirane ring at 70.9 and δ CH of the epoxy ring at 50.9. 29 Si NMR spectra showed the two peaks at δ −108 ppm and δ 7.2 ppm for Q 4 species [Si(OSi) 4 ] and M 1 species [Si(OSi)(CH 3 ) 2 CH 2 ], respectively, and there was hardly any change with the G 0 A. Therefore, it may be concluded that the G 0 B dendrimer was synthesized successfully.…”
Section: Nmr Studiesmentioning
confidence: 86%
See 3 more Smart Citations
“…13 C NMR spectra showed that the signals for δ SiCH 3 appeared at 0.1 ppm, for δ SiCH 2 at 14.1 ppm, δ -CH 2 of the Si-CH 2 -CH 2 -CH 2 -group appeared at 23.5 and 74.5 ppm, δ SiCH 2 of the oxirane ring at 44.6 ppm, δ CH 2 of the O-CH 2 -oxirane ring at 70.9 and δ CH of the epoxy ring at 50.9. 29 Si NMR spectra showed the two peaks at δ −108 ppm and δ 7.2 ppm for Q 4 species [Si(OSi) 4 ] and M 1 species [Si(OSi)(CH 3 ) 2 CH 2 ], respectively, and there was hardly any change with the G 0 A. Therefore, it may be concluded that the G 0 B dendrimer was synthesized successfully.…”
Section: Nmr Studiesmentioning
confidence: 86%
“…13 C NMR gave only one peak at δ 0.2 ppm, which may be assigned to δ CH 3 . 29 Si NMR showed two peaks at δ −108 and δ 8.5 ppm. The peak at higher field may be assigned to structural species Q 4 [Si(OSi) 4 ] and corresponds to a silicon atom attached to four silicon species via oxygen bridges.…”
Section: Nmr Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The peripheral hydrophobic modification of commercially available, water-soluble poly(propylene imine) and poly(amidoamine) dendrimers has proved to be a convenient strategy for producing amphiphilic dendrimers in which all or some of the surface groups are hydrophobized. Fully hydrophobized dendrimers, which are referred to as having a hydrophilic dendrimer core-hydrophobic shell architecture, usually exhibit ordered aggregation on a nanoscopic scale with peculiar shapes and morphology.…”
Section: Introductionmentioning
confidence: 99%